THE EFFECT OF ROLE PLAY METHOD ON ADOLESCENTS’ KNOWLEDGE ABOUT BULYYING PREVENTION - Negara, Moch. Hakim Setya; Kusbiantoro, Dadang; Susanti, Inta (Journal of Vocational Nursing, 2025)
Introduction: Adolescence is a transition period from childhood to adulthood. As a teenager, individuals will begin to recognize a wider environment than family, and the socialization experienced by individuals will also be wider. Role-playing or role-playing methods as a treatment for bullies in schools so that they can prevent bullying activities that continue to recur. Methods: This study aims to determine the effect of the role-play method on preventing bullying in teenagers at SMP Negeri 1 Karanggeneng. This study used a quantitative pre-experimental design method with a one-group pre-test-post-test design approach. The population was 471 patients, with a sample of 114 with a simple random sampling technique. Data analysis used the Wilcoxon test. Results: The results of this study obtained 114 respondents for increasing bullying knowledge prevention with the final result being an increase of 94.7% in the good category, 5.3% in the sufficient category, and 0% in the less category. In the statistical test using Wilcoxon, the z value was obtained = -9.858 with a significant p-value = 0.000 where the significance standard p <0.005, meaning that there is an influence of the role-play method on the level of bullying cases in adolescents at SMP Negeri 1 Karanggeneng before and after. Conclusions: The use of role-play techniques in adolescent students to improve bullying prevention knowledge has a significant influence. The use of role-play techniques has significance in increasing bullying prevention, so it can lead to increased knowledge in adolescents of SMP Negeri 1 Karanggeneng.